Origins of Pictures: Anthropological Discourses in Image Science - Sachs-Hombach, Klaus (EBL-Schweitzer, 2014)
Copyright; Table of Contents; Klaus Sachs-Hombach / Jörg R. J. Schirra; Introduction; I.Methodological Aspects of Picture Anthropology; Iain Davidson; Origins of Pictures: An Argument for Transformation of Signs; Jean Clottes; Consequences of the Discovery and Study of the Chauvet Cave; Lambros Malafouris; Learning to See: Enactive Discovery and the Prehistory of Pictorial Skill; Christa Sütterlin; Early Face Representation as Proto- or Archetype of Generalized Human Face Perception; II.Relation between Empirical Anthropological Investigations and Synthetic Philosophical Investigations